2018
DOI: 10.22159/ajpcr.2018.v11i10.26620
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gambier Extract on the Levels of Malondialdehyde, Superoxide Dismutase, and Blood Glucose in Type 2 Diabetes Mellitus Patients

Abstract: Objective: Diabetes mellitus is a disease associated with dysfunction of pancreatic β-cells and oxidative stress. A treatment which can reduce the impact of oxidative stress may be beneficial in the treatment of diabetes. Therefore, this study aimed to investigate the effect of gambier extract on the levels of malondialdehyde (MDA), superoxide dismutase (SOD), and blood glucose level (BGL) in type 2 diabetes mellitus (T2DM).Methods: This research was a randomized clinical study consisted of two groups, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…Gambier is known to prevent various diseases because it is both anti-inflammatory and a strong antioxidant. Pane et al (2018) reported that gambier can reduce blood glucose levels in T2DM patients by increasing levels of superoxide dismutase resulting in a decrease in malondialdehyde formation and an increase in pancreatic function in producing insulin. In the present study, we suggested that the habit of chewing betel can control BGL because of the efficacy of gambier which is one of the components in betel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gambier is known to prevent various diseases because it is both anti-inflammatory and a strong antioxidant. Pane et al (2018) reported that gambier can reduce blood glucose levels in T2DM patients by increasing levels of superoxide dismutase resulting in a decrease in malondialdehyde formation and an increase in pancreatic function in producing insulin. In the present study, we suggested that the habit of chewing betel can control BGL because of the efficacy of gambier which is one of the components in betel.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-oxidant catechin molecules in gambier are safe, and identified as the main bioactive compounds in gambier (Anggraini et al, 2011). Catechins can improve diabetes and its complications by modifying oxidative stress (p<0.05) (Pane et al, 2018;Samarghandian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such herb is gambier (Uncaria gambir Roxb.) 5 , which has antioxidant effects and lowers blood glucose when treating type 2 diabetes mellitus (T2DM). There are also bangun-bangun leaves (Coleus amboinicus), which are believed to be effective in relieving pain when distilled as ethanol and water extract 6 .…”
Section: Introductionmentioning
confidence: 99%
“…One such herb is such as gambier (Uncaria gambir Roxb.) 4 , which has antioxidant effects and lowers blood glucose when treating type 2 diabetes mellitus. There is also bangun-bangun leaves (Coleus amboinicus), which are believed to be effective in relieving pain when distilled as ethanol and water extract 5 .…”
Section: Introductionmentioning
confidence: 99%